2010
DOI: 10.1007/s11240-010-9890-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient indirect induction of protocorm-like bodies and shoot proliferation using field-grown axillary buds of a Lycaste hybrid

Abstract: This work presents a rapid and reliable micropropagation method for a Lycaste hybrid using a fieldgrown axillary bud culture system. Intact buds (2-4 mm in length) were excised from a mature pseudobulb and were cultured in half-strength MS basal medium, which was supplemented with 0.5 mg l -1 benzyladenine (BA), 1.0 mg l -1 thidiazuron (TDZ) and 2% (w/v) sucrose. After 2 months, the calli exhibited vigorous growth and eventually turned green, forming protocorm-like bodies (PLBs) originating in the surface of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…It has been reported that AC remove light in the media and provides a suitable physical environment for the rhizosphere and facilitates rooting in A. andreanum (Gantait et al 2008). In accordance to our report on this bi-phasic (shoot and subsequent root formation) conversion of PLBs to plantlets, Huang and Chung (2011) have also used a similar strategy for shoot (cytokinins BA and TDZ combination) and root (auxins IBA or NAA) formation of PLBs of Lycaste hybrid. A similar method of step wise conversion of PLBs was also reported earlier by Hossain et al (2010) in Cymbidium giganteum Wall.…”
Section: Conversion Of Plb In Shoot and Rootsupporting
confidence: 89%
“…It has been reported that AC remove light in the media and provides a suitable physical environment for the rhizosphere and facilitates rooting in A. andreanum (Gantait et al 2008). In accordance to our report on this bi-phasic (shoot and subsequent root formation) conversion of PLBs to plantlets, Huang and Chung (2011) have also used a similar strategy for shoot (cytokinins BA and TDZ combination) and root (auxins IBA or NAA) formation of PLBs of Lycaste hybrid. A similar method of step wise conversion of PLBs was also reported earlier by Hossain et al (2010) in Cymbidium giganteum Wall.…”
Section: Conversion Of Plb In Shoot and Rootsupporting
confidence: 89%
“…However, meristems can be formed indirectly from unspecialized cells in calluses or culture suspensions (Yancheva, Golubowicz, Fisher, Lev-Yadun, & Flaishman, 2003;Gahan & George, 2008). The direct and indirect origin of adventitious buds has been described for monocotyledons (e.g., Paphiopedilum spp., Chen, Chen, & Chang, 2004; Lycaste spp., Huang & Chung, 2011), dicotyledons (e.g., Citrus spp., Almeida et al, 2003; Malus x domestica, Yancheva et al, 2003;Passiflora edulis, Fernando et al, 2007;Centaurea ultreiae, Mallón, Rodríguez-Oubiña, & González, 2011) and conifers (e.g., Pinus massoniana, Zhang, Wei, Xi, & Shi, 2006;P. pinea, Cuesta, Rodríguez, Centeno, Ordas, & Fernán-dez, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…(Protocorm Like Body) 및 뿌리줄기(rhizome)등을 이용한 조직 배양 방법은 일반적인 번식방법이 어려운 식물체에서 사용 되어왔다 (Ng and Saleh 2011;Huang and Chung 2011;Rayirath et al 2011;Torres-Morán et al 2010). 이러한 기내 비대경 생산을 통한 번식방법은 구황작물에서 가장 큰 문제가 되고 있는 바 이러스 및 병에 대한 저항성을 가진 무병주(virus or diseasefree plantlets)의 대량생산을 가능하게 하며, 작물의 특성상 장기저장과 이동이 어려운 유전자원의 저장 및 이동을 보다 용이하게 하였다 (Uchendu et al 2016).…”
Section: 문제점을 극복하기 위해 조직배양을 이용한 다양한 기술이 개발되었으며 이중 기내비대경(Microtuber)을unclassified